Accelerometer-Assessed Physical Activity on School Days With and Without Physical Education Among Thai Primary School Students - Areekul Amornsriwatanakul; Songdhasn Chinapong; Korntawat Klinchan; Vimolmas Tansathitaya; Hanif Abdul Rahman; Michael Chia; Charinthip Manyuen; Phong-ek Suksai; Taweesak Sawangmek; Apanchanit Siripatt; Nopparut Poblarp; Phennipha Phunsawat; et al. (Journal of Physical Activity and Health, 2026)
Background : This study examined accelerometer-assessed physical activity (PA) among Thai primary school students on days with and without physical education (PE) class and explored how demographic and contextual factors influence children’s moderate to vigorous PA (MVPA) during the school day. Methods : This cross-sectional study involved Thai primary students (grades 5–6) from 5 areas across Thailand. Physical activity was assessed using accelerometers, and demographics were collected via a PE questionnaire. Analyses included Wilcoxon signed-rank test for PA intensity comparisons, and factors associated with MVPA were examined using multilevel generalized linear regression. Results : A total of 799 students participated. On PE days, they engaged in more light-intensity PA: 103.5 (110.7) minutes vs 85.8 (84.2) minutes. Regional and school-type differences were observed, with greater MVPA among students in the Northeast (71.8 vs 33.9 min, P < .001) and those attending noncity schools (40.2 vs 31.0 min, P = .014). Regression analyses showed that students who slept